Daily honey consumption does not change CYP3A activity in humans - Rudofsky, Leonie; Burhenne, Jürgen; Weiß, Johanna; Völker, Michael; Unger, Matthias; Mikus, Gerd; Haefeli, Walter E. (Journal of clinical pharmacology, 2011)
Several studies investigating the interaction of honey and drug-metabolizing enzymes showed controversial results, with some suggesting that honey induces CYP3A-mediated metabolism in mammals and humans. This clinical trial was conducted to determine the effect of repeated honey administration on human CYP3A enzyme activity using midazolam as a marker substance. In a randomized, single-blind, parallel-group study, 20 healthy volunteers were randomly assigned to receive either honey (2 × 20 g/d) or artificial honey (2 × 20 g/d) over a period of 10 days. To determine intestinal and hepatic CYP3A activity, oral (4 mg) and intravenous (2 mg) midazolam was administered in a semi-simultaneous way before honey administration, after the last honey administration, and 1 and 6 days thereafter. At baseline after oral midazolam, the partial metabolic clearance was similar in both groups (honey: 917.8 ± 234.6 mL/min vs artificial honey: 973.5 ± 373.8 mL/min). Ten days of honey administration did not change partial metabolic clearance (honey: 1016 ± 268 mL/min vs artificial honey: 1043 ± 450 mL/min), which was also true 1 and 6 days later. Neither honey nor artificial honey in amounts usually consumed affected the intestinal and hepatic CYP3A activity in healthy volunteers.